К морфологии и экологии подкаменщика туркестанского (Cottus spinolosus Kessl.) Ферганской долины - Максунов, В.А. (Вестник зоологии, 1973)
New data are given on morphology and ecology of Cottus spinolosus K e s s 1. - an endemic species of the Syr Daria basin. Comparison of morphological peculiarities resulted in an assumption on the existence of different populations of this species in various rivers of the basin.